2020
DOI: 10.1007/s10557-019-06924-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating Angiopoietin-Like Protein 8 Levels Are Associated with Thoracic Aortic Dissection and Higher Inflammatory Conditions

Abstract: Purpose Thoracic aortic dissection (TAD) is characterized by an inflammatory response. Angiopoietin-like protein 8 (ANGPTL8) is a hormone involved in the regulation of lipid metabolism and inflammation. However, the relationship between ANGPTL8 and TAD remains unknown. Methods This case-control study included 78 TAD patients and 72 controls. The aortic diameter was evaluated by computed tomography and used to assess TAD severity. Circulating ANGPTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
(45 reference statements)
1
22
1
Order By: Relevance
“…Notably, compared with that in non-AAD tissues, the fraction of monocytes and macrophages in AAD tissues was significantly increased in both the training set and validation set, which indicates that the results were reliable. Analysis of the correlations between hub genes and CD14 and CD68, cell markers of monocytes and macrophages, in both the training set and validation set was performed to investigate the mechanism of immunoinflammatory responses in the development of AAD (7,21,24).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, compared with that in non-AAD tissues, the fraction of monocytes and macrophages in AAD tissues was significantly increased in both the training set and validation set, which indicates that the results were reliable. Analysis of the correlations between hub genes and CD14 and CD68, cell markers of monocytes and macrophages, in both the training set and validation set was performed to investigate the mechanism of immunoinflammatory responses in the development of AAD (7,21,24).…”
Section: Discussionmentioning
confidence: 99%
“…The ANGPTL family has also been reported to play important roles in angiogenesis, inflammation, and cancer and has recently been implicated in the regulation of stem cell activity [12,[49][50][51][52]. The circulating levels of ANGPTL8/betatrophin are increased under high levels of inflammation [53]. Inflammatory stimuli have been reported to induce the expression of ANGPTL8/ betatrophin, which negatively regulates the activation of one of the most important central regulators of inflammation, nuclear factor-κB (NF-κB), to regulate inflammation [54].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that ANGPTL8 may promote the development of DN through inflammatory mechanisms. ANGPTL8 has been proven to positively correlate with hs-CRP, leading to higher inflammatory conditions in thoracic aortic dissection ( 37 ). Sinha SK et al ( 38 ) reported that elevated serum levels of hs-CRP were associated with, and possibly influenced the development of DN, even for those without DM at baseline.…”
Section: Discussionmentioning
confidence: 99%